Chemical exchange saturation transfer of the cervical spinal cord at 7 T. (26th July 2016) - Dula, Adrienne N.; Pawate, Siddharama; Dethrage, Lindsey M.; Conrad, Benjamin N.; Dewey, Blake E.; Barry, Robert L.; Smith, Seth A.
Abstract : High‐magnetic‐field (7 T) chemical exchange saturation transfer (CEST) MRI provides information on the tissue biochemical environment. Multiple sclerosis (MS) affects the entire central nervous system, including the spinal cord. Optimal CEST saturation parameters found via simulation were implemented for CEST MRI in 10 healthy controls and 10 patients with MS, and the results were examined using traditional asymmetry analysis and a Lorentzian fitting method. In addition, T 1 ‐ and T 2 *‐weighted images were acquired for lesion localization and the transmitted B 1 + field was evaluated to guide imaging parameters. Distinct spectral features for all tissue types studied were found both up‐ and downfield from the water resonance. The z spectra in healthy subjects had the expected z spectral shape with CEST effects apparent from 2.0 to 4.5 ppm. The z spectra from patients with MS demonstrated deviations from this expected normal shape, indicating this method's sensitivity to known pathology as well as to tissues appearing normal on conventional MRI. Examination of the calculated CESTasym revealed increased asymmetry around the amide proton resonance (Δ ω = 3.5 ppm), but it was apparent that this measure is complicated by detail in the CEST spectrum upfield from water, which is expected to result from the nuclear Overhauser effect. The z spectra upfield (negative ppm range) were also distinct between healthy and diseased tissue, and could not be ignored, particularly when considering the conventional asymmetry analysis used to quantify the CEST effect. For all frequencies greater than +1 ppm, the Lorentzian differences (and z spectra) for lesions and normal‐appearing white matter were distinct from those for healthy white matter. The increased frequency separation and signal‐to‐noise ratio, in concert with prolonged T 1 at 7 T, resulted in signal enhancements necessary to detect subtle tissue changes not possible at lower field strengths. This study presents CEST imaging metrics that may be sensitive to the extensive and temporally varying biochemical neuropathology of MS in the spinal cord. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Optimal chemical exchange saturation transfer (CEST) saturation parameters found via simulation were implemented for CEST MRI in 10 healthy controls and 10 patients with multiple sclerosis (MS), and results were examined using traditional asymmetry analysis and the Lorentzian fitting method. Distinct spectral features for all tissue types studied were found both up‐ and downfield from the water resonance. The z spectra in healthy subjects had the expected z spectral shape with CEST effects apparent from 2.0 to 4.5 ppm, whereas the z spectra from patients with MS demonstrated deviations from this expected normal shape, indicating this method's sensitivity to known pathology, as well as tissues appearing normal on conventional MRI.